Optimalizing the Role of Information Quality, Interactivity, and TikTok Shop Live Streaming in Shaping Impulsive Buying Among Generation Z TikTok Shop Users - Puji Sumber Lestari; Setya Indah Isnawati (International Forum of Researchers and Lecturers, 2026)
The rapid development of digital technology has transformed the landscape of electronic commerce, encouraging consumers to adopt online shopping through social commerce platforms. TikTok Shop has emerged as one of Indonesia's fastest-growing social commerce platforms by integrating entertainment, social interaction, and e-commerce into a single application. Various features, including information quality, interactivity, and live streaming, are believed to influence consumers' purchasing behavior, particularly among Generation Z, who actively engage with digital platforms. However, limited studies have comprehensively examined the combined influence of these three variables on impulsive buying behavior among Generation Z TikTok Shop users in regional areas such as Ungaran. Therefore, this study aims to analyze the role of information quality, interactivity, and TikTok Shop live streaming in shaping impulsive buying among Generation Z users. This research employs a quantitative approach using a survey method. Primary data will be collected through questionnaires distributed online using Google Forms to respondents selected through purposive sampling. A total of 96 respondents will participate in this study based on the Lemeshow sampling formula. The collected data will be analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The findings are expected to provide empirical evidence regarding the influence of information quality, interactivity, and live streaming on impulsive buying behavior while offering practical implications for digital marketers in optimizing marketing strategies through TikTok Shop.